Disseminated Histoplasmosis in Central California Seen in an Immunocompromised Patient - Kishan Ghadiya BS; Robert Dunn MD; Gurpal Singh MD; Hobart Lai MD; Ralph Garcia-Pacheco MD (SAGE Publishing, 2023)
Histoplasma capsulatum is a dimorphic fungus found in certain parts of North, Central, and South America. Transmission is primarily through airborne inoculation from inhaled fungal microconidia. Histoplasmosis is typically a self-limited mycosis; however, in patients with immunodeficiency, disseminated disease can occur and may lead to high disease burden. This report studies a case of disseminated histoplasmosis in a patient newly diagnosed with human immunodeficiency virus. His presentation on admission was consistent with infectious pulmonary granulomatous disease, and further imaging and laboratory results showed evidence of multi-organ involvement. It is likely his presentation in Central California was a reactivation infection after inoculation in Central America many years ago.